Effects of Escitalopram on Endoplasmic Reticulum Stress and Oxidative Stress Induced by Tunicamycin - Yang, Lixia; Chen, ZhengHong; Li, Jie; Ding, PengJin; Wang, Yiming (Frontiers in Neuroscience, 2021)
Background: Major depressive disorder (MDD) was reported to be associated with endoplasmic reticulum stress (ERS) combined with oxidative stress (OS) (ERS/OS). Here, we aimed to investigate the effects of escitalopram (ESC) on blood-brain barrier (BBB) permeability and ERS/OS-related pathways in brain microvascular endothelial cells (bEnd.3 cells) induced by tunicamycin (TM).Methods: bEnd.3 cells were divided into four groups: control, TM, ESC, and ESC+TM groups. CCK-8 and flow cytometry were used to detect cell survival and apoptosis, respectively. The expression levels of proteins involved in cell permeability and ERS/OS-related pathways were assessed by western blot and immunofluorescence. Malondialdehyde (MDA) concentration and superoxide dismutase (SOD) activity were determined by commercial kits. Results: We revealed that TM-induced bEnd.3 cells exhibited remarkably decreased viability and increased apoptosis rate, while ESC treatment reversed these changes. Additionally, TM treatment resulted in markedly increased PERK, GRP78, ATF6, XBP1, and CHOP protein expression levels. On the contrary, the expression of PERK, GRP78, XBP1, and CHOP was obviously reduced in TM-induced bEnd.3 cells after ESC treatment. Moreover, TM significantly reduced the expression of p-eNOS and P-gp and increased the expression of CAMKII and MMP9 compared with the control group. However, ESC reversed these changes in TM-induced bEnd.3 cells. Furthermore, the expression of SOD was significantly decreased, while MDA was significantly increased by TM treatment. In contrast, the expression of SOD was dramatically increased, while MDA was remarkably decreased by ESC treatment. Conclusion: Our results demonstrated that ESC can inhibit ERS/OS and BBB permeability of TM-induced bEnd.3 cells. ESC may alleviate cognitive impairment and prevent comorbidities in MDD patients through ERS/OS.